Nota sobre efeitos do modo de localização de fertilizantes na cultura do feijão (Phaseoulus vulgaris L) - do Amaral, Flávio A L; M de Oliveira , Laede; Domingos Galvão , José; Vieira, Clibas (Revista Ceres, 2025)
In two experiments with edible beans (Phaseolus vulgaris L.), the following methods of fertilizer placement were compared: (a) on top of the soil in two bands to the side of the row; (b) mixed with the soil in the row; (c) below the seeds, but not in contact with them; (d) in direct contact with the seeds; (e) above the seeds, but not in contact with them; (f) below and to the side of the seeds in two bands; (g) below and to the side of the seeds in one band.